Rural livelihood, accumulation and class formation in post-development-induced displacements in Zimbabwe - Fadzai Chipato (Cogent Social Sciences)
Land transactions and deals often lead to displacements and removal of people from their traditional and ancestral lands, disrupting rural livelihoods and causing significant socio-economic consequences for affected communities. Zimbabwe has a long history of displacements dating back to the colonial period. Post-independence Zimbabwe is dominated by ‘black people on black people’ displacements that are mainly done in the name of development activities. This study examines the emerging rural livelihoods, forms of accumulation and class formation among households displaced by the Tokwe Mukosi Dam project in Zimbabwe. Findings reveal that three-quarters of displaced livelihoods depend on survivalist strategies 10 years after the displacement, and these livelihoods are dropping out and in hanging mode. There is a shift from agrarian to non-agrarian livelihood strategies driven by reduced access to land and constrained spatial resources. This article argues that agriculture is not a viable livelihood strategy in Chingwizi resettlement, and for upward mobility to materialise, people are diversifying their strategies with migration, rural entrepreneurship and the supply of labour to community projects that are underway. Four distinct classes – poor, semi-poor, middle and rich peasantry – are emerging, shaped by non-agrarian income sources and demographic factors. These findings contribute to debates on displacement and rural differentiation, offering insights into interventions to mitigate inequalities in resettlement contexts.